Past, present, and future of craniofacial superimposition: Literature and international surveys. Issue 4 (July 2015) - Huete, Maria Isabel; Ibáñez, Oscar; Wilkinson, Caroline; Kahana, Tzipi
<x xml:space="preserve">Abstract</x> Highlights Review of craniofacial superimposition methods. Analysis of the current situation of craniofacial superimposition. Discussion of the future challenges and reliability of craniofacial superimposition.